Development of a Patient‐centered Outcome Measure for Emergency Department Asthma Patients. (24th April 2017) - Samuels‐Kalow, Margaret E.; Rhodes, Karin V.; Henien, Mira; Hardy, Emily; Moore, Thomas; Wong, Felicia; Camargo, Carlos A.; Rizzo, Caroline T.; Mollen, Cynthia
Abstract: Background: Measuring outcomes of emergency care is of key importance, but current metrics, such as 72‐hour return visit rates, are subject to ascertainment bias, incentivize overtesting and overtreatment at initial visit, and do not reflect the full burden of disease and morbidity experienced at home following ED care. There is increasing emphasis on including patient‐reported outcomes, but the existing patient‐reported measures have limited applicability to emergency care. Objective: The objective was to identify concepts for inclusion in a patient‐reported outcome measure for ED care and assess differences in potential concepts by health literacy. Methods: A three‐phase qualitative study was completed using freelisting and semistructured interviewing for concept identification, member checking for concept ranking, and cognitive interviewing for question development. Participants were drawn from three tertiary care EDs. Parents of patients (pediatric) or patients (adult) with asthma completed a demographic survey and an assessment of health literacy. Phase 1 participants also completed a freelisting exercise and qualitative interview regarding the definition of success following ED discharge. Phase 2 participants completed a member checking survey based on concepts identified in Phase 1. Phase 3 was a pilot of trial questions based on the highest‐ranked concepts from Phase 2. Results: Phase 1 enrolled 22 adult patients and 37 parents of pediatric patients. Phase 2 enrolled 41 adult patients and 200 parents. Phase 3 involved 15 parents. Across all demographic/literacy groups, Phase 1 participants reported return to usual activity and lack of asthma symptoms as the most important markers of success. In Phase 2, symptom improvement, medication use and access, and asthma knowledge were identified as the most important components of the definition of post‐ED discharge success. Phase 3 resulted in five questions for the proposed measure. Conclusions: A stepwise qualitative process can identify, rank, and formulate questions based on patient‐identified concepts for inclusion in a patient‐reported outcome measure for ED discharge. The four key concepts identified for inclusion: symptom improvement, medication access, correct medication use, and asthma knowledge are not measured by existing quality metrics.